Analysys of Blind adaptive multiuser detection receivers - Rangisetty, Nirmaladevi; Kishan Rao, K. (Transactions on Engineering and Computing Sciences, 2015)
In this paper, blind adaptive multiuser detection with Mean Output Energy (MOE) are designed in receivers for synchronous MC-DS-CDMA systems in Rayleigh fading channels. Pre and post detection in multiuser detectors are implemented in the system to detect their effects in the outputs. On the basic of the delayed received signals, we proposed Affine Projection Algorithm-link multiuser detector (APA) and its performance is evaluated with the existing multiuser blind detectors (Normalized blind LMS and Kalman Filter). Compared to existing multiuser detectors APA-link detector outperformed the BER performance and provided a tradeoff between performance and computation cost. The analysis if further extended by implementing, decorrelating multiuser detector based receivers in SC-DS-CDMA and MC-DS-CDMA to eliminate the MAI caused by other users.